Final Results of National Surveillance of Childhood Tuberculosis in Canada: 2013–2016 - Giroux, Ryan (Paediatr Child Health, 2018)
BACKGROUND: There is little detailed epidemiologic and clinical data about tuberculosis (TB) disease in children in Canada. OBJECTIVES: This study characterizes the epidemiologic, clinical, and treatment data for all cases of TB in children under age 15 in Canada surveyed through the Canadian Paediatric Surveillance Program’s (CPSP) Childhood Tuberculosis Study from October 2013 to September 2016. DESIGN/METHODS: New active TB cases were identified through a monthly form sent by the CPSP to approximately 2500 active paediatricians, paediatric subspecialists, and select non-paediatricians who manage childhood TB. For cases meeting inclusion criteria, a detailed questionnaire was sent to the treating physician to collect clinical, epidemiological, and treatment data, followed by 6-month follow-up surveys until 6 months after treatment completion. Cases were reviewed by at least one TB specialist for inclusion and classification of disease. RESULTS: Of 285 unique incident cases reported, 188 cases met inclusion criteria, returned a detailed questionnaire, and were classified. Selected demographic data are shown in Table 1. 92% of cases had intrathoracic involvement (N=172, 91%), but a minority were confirmed by culture or nucleic acid amplification (62/172, 36%). The most common sites of intrathoracic involvement were lymph nodes (N=118, 69%) and lungs (N=54, 31%). There were 143 attempted respiratory microbiological studies, with 32 (22%) yielding a positive culture or NAAT in sputum and 33 (23%) in gastric aspirate. Highest yield was in the 10+ age group with 54% (20/37) positivity. 31 cases of extrathoracic TB were recorded, with 19/35 (54%) having simultaneous intrathoracic TB. The most common forms of extrathoracic TB included CNS or meningeal disease (N=13) and extrathoracic lymphadenopathy (N=11). Miliary or disemminated disease (2 or more non-continguous sites involved) was found in 15 cases (8%). 16 cases reported at least one adverse drug reactions, with pyrazinamide (N=10) and isoniazid (N=5) being most common. 4 children were hospitalized and the most common ADR was hepatotoxicity. There was one case of multi-drug resistant TB. CONCLUSION: This study suggests a high incidence of TB in Inuit and First Nations children, as well as a higher proportion of extrathoracic TB and greater success in culture positivity in children aged 10+. It also shows a significant number of adverse drug reactions to anti-TB treatment. Further analysis of this data will serve to refine practice in monitoring, detecting, and treating this infection.